2007
DOI: 10.1111/j.1095-8312.2007.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and somatometric growth of long-tailed macaques (Macaca fascicularis fascicularis) in Singapore

Abstract: Crab-eating, or long-tailed, macaques [Macaca fascicularis (Raffles, 1821)] have been studied extensively throughout their distribution in South and South-east Asia. Despite this extensive body of research, the island population of long-tailed macaques from Singapore remains virtually undescribed. In the present study, we compare the morphometric variability and patterns of growth observed in a population sample from Singapore with a composite sample from Thailand, north of the Isthmus of Kra. The results of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 49 publications
(78 reference statements)
1
29
1
Order By: Relevance
“…The authors of that study did not, however, find a relationship between island area and the degree of body size change. A recent comparison of insular populations of M. fascicularis without reference to mainland core populations also did not find a significant relationship between island size and body size [Schillaci et al, 2008].…”
Section: The Island Effectmentioning
confidence: 79%
See 1 more Smart Citation
“…The authors of that study did not, however, find a relationship between island area and the degree of body size change. A recent comparison of insular populations of M. fascicularis without reference to mainland core populations also did not find a significant relationship between island size and body size [Schillaci et al, 2008].…”
Section: The Island Effectmentioning
confidence: 79%
“…The study of latitudinal and insular variation in the genus Macaca has been a topic of considerable research [e.g., Albrecht, 1978Albrecht, , 1980Albrecht, , 1983Fooden, 1975Fooden, , 1979Fooden, , 1991Fooden, , 1995Fooden, , 2006Fooden & Albrecht, 1993, 1999Hamada et al, 2008;Schillaci et al, 2007Schillaci et al, , 2008. Most of this research has identified latitudinal trends in macaque body size that are often, though not always, consistent with Bergmann's [Bergmann, 1847] and Allen's [Allen, 1877] rules.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating this, the cardiac image was also described in radiographic studies of the cardiac silhouette in monkeys of the Macaca nigra and Macaca tonkeana species (Schillaci et al 2007(Schillaci et al , 2008.…”
Section: Radiographic Pattern Of Thoracic Structuresmentioning
confidence: 93%
“…Radiographs in ventrodorsal projection favored the visualization of the pleural reϐlec-tion along the line where the accessory and left caudal lung lobes meet (Schillaci et al 2007). In these animals, the boundaries of diaphragmatic cupola could be distinguished, regardless of the x-ray beam angle, the opposite to what occurs with dogs and cats (Alves et al 2009).…”
Section: Radiographic Pattern Of Thoracic Structuresmentioning
confidence: 99%
See 1 more Smart Citation